Opioid switching in cancer pain: From the beginning to nowadays - Mercadante, Sebastiano; Bruera, Eduardo (Critical reviews in oncology/hematology, 2016)
•Opioid therapy in cancer patients should be highly individualized.•Opioid switching may allow to establish a more advantageous analgesia/toxicity relationship.•Indications for opioid switching require different modalities of intervention.•The knowledge of opioid pharmacology is of paramount importance.•Opioid switching requires meticulous monitoring, particularly when using high doses of opioids. Opioid switching is the process of changing from one opioid to another to obtain a satisfactory clinical balance between analgesia and adverse effects. This pharmacological technique has been introduced about 20 years ago to enhance the opioid response in advanced cancer patients with chronic pain. More information is now available. This review will examine many different aspects of opioid switching, including the history and evolution through the last decades, some clinical aspects based on the most recent experience, controversies on the indications, conversion ratios and modalities of switching in some specific circumstances, and evidence based recommendations.